Predictors of Clinical Outcome after Percutaneous Coronary Intervention in Hemodialysis Patients with Acute Myocardial Ischemia Syndrome - Virk, Mutahir Abbas; Zia, Sheikh Muhammad Rehman; Noukhaiz, Namra; Javiad, Sahrish; Talal Asif, Ahmad; Hassan, Zoha; Qammar, Bilal (Indus Journal of Bioscience Research, 2024)
Introduction: Acute myocardial ischemia syndrome (AMIS), encompassing conditions such as unstable angina and acute myocardial infarction, is a major global health concern due to its significant morbidity and mortality rates. Objective: The main objective of the study is to find the predictors of clinical outcomes after percutaneous coronary intervention in hemodialysis patients with acute myocardial ischemia syndrome. Methodology: This retrospective cohort study was conducted at Army Cardiac Hospital Lahore from June 2023 to June 2024. Data were collected from 178 patients. Data were extracted from electronic health records, capturing comprehensive patient information across multiple domains. Results: The study analyzed data from 178 hemodialysis patients with mean age of 58.91 ± 8.02 years, with a gender distribution of 60% males and 40% females. Comorbid conditions were prevalent, with 65% having diabetes mellitus and 85% hypertension. Smoking was reported by 25% of individuals, and 40% had a history of myocardial infarction (MI) or revascularization. Laboratory parameters indicated anemia (mean hemoglobin: 10.2 ± 1.5 g/dL), low albumin levels (3.2 ± 0.5 g/dL), and systemic inflammation, as 70% had elevated CRP levels. Conclusion: It is concluded that hemodialysis patients undergoing PCI for acute myocardial ischemia syndrome face significant risks influenced by nutritional status, systemic inflammation, and comorbidities such as diabetes and cardiogenic shock